2000
DOI: 10.1016/s0550-3213(00)00096-1
|View full text |Cite
|
Sign up to set email alerts
|

Dirac quantization of open strings and noncommutativity in branes

Abstract: We apply the Dirac bracket quantization to open strings attached to branes in the presence of background antisymmetric field and recover an inherent noncommutativity in the internal coordinates of the brane.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
187
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(191 citation statements)
references
References 28 publications
(66 reference statements)
1
187
1
2
Order By: Relevance
“…In fact, for m = 0, Dirac quantization, with the boundary conditions regarded as constraints, has been used as an alternative. The problem that arises then is whether the boundary conditions should be regarded as first or second class, and this is not a trivial choice for they lead to different results [26] [27].…”
Section: Quantizationmentioning
confidence: 99%
“…In fact, for m = 0, Dirac quantization, with the boundary conditions regarded as constraints, has been used as an alternative. The problem that arises then is whether the boundary conditions should be regarded as first or second class, and this is not a trivial choice for they lead to different results [26] [27].…”
Section: Quantizationmentioning
confidence: 99%
“…In [10] the authors used the basic principles of Dirac quantization in order to discuss the noncommutativity of the internal coordinates of branes. It was shown that the noncommutativity of the coordinates of the open string-brane system is intrinsic, namely, there is no gauge in which the noncommutativity can be removed.…”
Section: Introductionmentioning
confidence: 99%
“…And the position of noncommutativity is always on the brane. In this work [10] the mixed boundary conditions were treated as the Dirac constraints and the quantization was obtained through the Dirac method without mode expansions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations